2021
DOI: 10.14445/22315381/ijett-v69i5p217
|View full text |Cite
|
Sign up to set email alerts
|

An Extensive Analytical Approach on Human Resources using Random Forest Algorithm

Abstract: The current job survey shows that most software employees are planning to change their job role due to high pay for recent jobs such as data scientists, business analysts and artificial intelligence fields. The survey also indicated that work life imbalances, low pay, uneven shifts and many other factors also make employees think about changing their work life. In this paper, for an efficient organisation of the company in terms of human resources, the proposed system designed a model with the help of a random… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Kangzhuoling is also a safe and efficient biological fungicide. Some scholars have used organic acid mold inhibitor KMC-LF2 to conduct mold proof test on corn and found that it has good mold proof effect [4]. In recent years, some researchers have also studied the control of microwave technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kangzhuoling is also a safe and efficient biological fungicide. Some scholars have used organic acid mold inhibitor KMC-LF2 to conduct mold proof test on corn and found that it has good mold proof effect [4]. In recent years, some researchers have also studied the control of microwave technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the basis of indepth understanding of forecasting mining technology, the multiple linear regression method is determined [11]. Through modeling, statistical index analysis, and significance test, the regression equation is obtained, the demand forecast for the number of enterprise personnel is carried out according to this, and the feasibility of the multiple regression model is verified [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The process from a single tree to a forest is solved. The problem of overfitting of a single decision tree increases the noise tolerance of the model [5]. There is also a big feature in the random forest algorithm -the Bagging method.…”
Section: Random Forest Algorithmmentioning
confidence: 99%